Foreign direct investment and regional convergence: an international approach - Raquel Díaz (European Regional Science Association (ERSA), 2004)
Since the middle 1980's, as consequence of the worldwide process of liberalization, there has been an important rise in international capital flows, especially Foreign Direct Investment (FDI). In particular, during the second half of 1990's, worldwide FDI inflows grew four times faster than domestic output, twice as fast as domestic investment and three times as fast as exports. However, the geographical distribution of these flows of international capital was highly uneven. The main receivers of these FDI inflows were the most-developed countries. The developing countries only received approximately 30% of the worldwide FDI inflows. At the same time, there has been a decrease in the speed of economic convergence among countries and regions. Between 1950 and 1990 the rate of convergence has been around 2% annually, but from the mid 1980's, this rate decreased to the 0.2%-0.5% level on an annual basis. Immediately, a question arises: could the very high share of international capital directed to the most-developed countries, be one reason for the slowdown in the rate of economic convergence?. Most studies on the effects of the internationalization of production processes in economic growth have identified the liberalization process with international trade, excluding the effects of FDI and its consequences on regional convergence. However, the liberalization process has increased not only trade, but also international capital flows. In this paper we address this last point. The main objective is to analyze the possible relationship among FDI and economic convergence. In particular, we present arguments which support the hypothesis that FDI inflows could be one of the elements helping to slowdown the speed of convergence in recent years. We show, on one hand, that FDI is an "engine of growth", the same as international trade. The main reason is that FDI is not merely a transfer of capital. FDI contributes to strengthening the economic structure on the host country, modernizes and internationalises it as well. FDI is usually accompanied by specific intangible assets of the transnational corporation, changes in production systems and/or technological innovations, among others. There is not doubt that all these factors generate positive growth effects in the target destination. On the other hand, we show that the main receivers of this FDI are not the developing countries. The developed countries, with more than two-thirds of the worldwide FDI inflows dominate the global picture. So, if these facts are analysed together, it is possible to show that the positive effects of FDI on economic growth are concentrated mainly in the most developed countries. From this point, the negative effect of FDI on economic convergence is an obvious result.
Keywords: 330